Testament Krzywoustego - Jureczko, Andrzej (Krakow : Krajowa Agencja Wydawnicza, 1988)
A short history of Poland in the 12th century.
Cover title.
Bibliography: p. [80].
Keywords: Boleslaw, -- III, -- King of Poland, -- 1085-1138.; Poland -- History -- 1138-1305.